Fostering Environmental Awareness among Santri through Religious Leadership and Local Cultural Wisdom: A Study in the Context of Pesantren Education - Masithoh, Fitria Nur; Fernandez, Dahlia; Rohmah, Miftakhur; Mansur, Mansur (Universitas Islam Negeri Raden Fatah Palembang, 2025)
The global ecological crisis necessitates educational approaches that foster holistic environmental awareness. Islamic boarding schools as traditional religious institutions, hold strategic potential in shaping ecological behavior through Islamic values and local wisdom. This study aims to examine the role of religious leaders and the integration of cultural values in developing green economic education within the Pondok Pesantren (Islamic Boarding School) context. A qualitative approach was employed using a case study design at Pondok Pesantren Lirboyo, Kediri, East Java. Data collection techniques included in-depth interviews, participatory observation, and analysis of relevant documents. The findings reveal that the exemplary conduct of Kiai and ustad plays a crucial role in internalizing ecological values among santri. Islamic principles such as khalifah, Amanah and tawazun are embedded in daily practices, including water conservation during ablution, waste management, and collective clean-up activities. These practices are reinforced by local wisdom such as guyub rukun, tirakat and nrimo ing pandum which shape collective and sustainable ecological awareness. The study develops an organic and contextual model of green economic education rooted in the spirituality and cultural traditions of the Pesantren community. These findings confirm that environmental education does not necessarily rely on formal curricula but can emerge from grounded religious and social practices. This model offers a valuable contribution to the development of alternative sustainable education approaches, particularly in value-based and tradition-oriented communities such as Pesantren.